El paciente diabético y sus pies: maximizando la funcionalidad. Aportes desde la Medicina Física y Rehabilitación - Rotter P., Karin (Revista Hospital Clínico Universidad de Chile, 2010)
The prevalence and costs of the different foot complications in diabetic patients are high, but most of them are preventable managing the risk factors. The field of Physical Medicine and Rehabilitation contributes to the management to all the spectrum from preventive measures for foot ulcers and recurrences, guidence in the selection of functional surgeries till favoring the maximum of functionality of those with partial or mayor foot amputations.